Simultaneous EEG/MEG yields complementary information of nociceptive evoked responses - Mahmutoglu, Mustafa A.; Rupp, André; Baumgärtner, Ulf (Clinical neurophysiology, 2022)
Objective - Nociceptive stimuli have been studied either by dipolar modelling using electroencephalography (EEG) or magnetoencephalography (MEG), but rarely using both techniques simultaneously. This study aims to investigate the spatiotemporal representation of cortical activity in response to non-nociceptive (tactile) and nociceptive (laser) stimuli using parallel EEG-MEG recordings. - Methods - We performed simultaneous EEG and MEG recordings in 12 healthy subjects by applying pneumatic tactile and nociceptive laser stimuli on the right- and left-hand dorsum. We analyzed brain responses for both modalities and methods by means of global field power (GFP), and dipole source locations, strengths and orientations calculated in the depth to identify similarities and differences. - Results - Prominent GFP peaks were similar in EEG and MEG for tactile responses but different for nociceptive responses. - Conclusions - Methodically, MEG was superior to EEG in detecting the earliest nociceptive laser-evoked components with earlier latency in primary- and secondary somatosensory cortices, whereas EEG was superior to MEG in detecting late nociceptive components due to radially oriented deeper cortical activity. - Significance - EEG and MEG revealed in part differential nociceptive waveform patterns, peak latencies, and source orientations, making combined recordings favorable to examine pain-related activity as a whole in high temporal-spatial resolution.
Online verfügbar: 24. August 2022, Artikelversion: 7. September 2022
Gesehen am 23.09.2024